2014
DOI: 10.1136/bmjopen-2014-005498
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes, access and anguish: a qualitative interview study of staff and patients’ experiences of diabetic retinopathy screening

Abstract: ObjectiveTo examine the experiences of patients, health professionals and screeners; their interactions with and understandings of diabetic retinopathy screening (DRS); and how these influence uptake.DesignPurposive, qualitative design using multiperspectival, semistructured interviews and thematic analysis.SettingThree UK Screening Programme regions with different service-delivery modes, minority ethnic and deprivation levels across rural, urban and inner-city areas, in general practitioner practices and pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
96
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(121 citation statements)
references
References 24 publications
4
96
1
2
Order By: Relevance
“…To our knowledge no study has been undertaken in New Zealand to understand the barriers to attending DR screening. In England, a qualitative study of attenders, non‐attenders and screening staff identified factors affecting uptake included convenience of screening location, transport safety, appointment length and side effects of pupil dilation . In Australia, young adults were found to experience more barriers to attending DR screening compared to older adults, and these barriers tended to accumulate .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge no study has been undertaken in New Zealand to understand the barriers to attending DR screening. In England, a qualitative study of attenders, non‐attenders and screening staff identified factors affecting uptake included convenience of screening location, transport safety, appointment length and side effects of pupil dilation . In Australia, young adults were found to experience more barriers to attending DR screening compared to older adults, and these barriers tended to accumulate .…”
Section: Discussionmentioning
confidence: 99%
“…In England, a qualitative study of attenders, nonattenders and screening staff identified factors affecting uptake included convenience of screening location, transport safety, appointment length and side effects of pupil dilation. 36 In Australia, young adults were found to experience more barriers to attending DR screening compared to older adults, and these barriers tended to accumulate. 37 These factors are conceivably all at play in New Zealand, in addition to gaps in the health literacy, cultural competence and safety of DR services.…”
Section: Implications For Practice and Researchmentioning
confidence: 99%
“…Many people with diabetes experience competing health problems that can overshadow concerns with their eyes. For some, missing a screening appointment might be attributable to a temporary illness or health problem [24,25,28], but for others it was a consequence of comorbidities [26,43,53] or the burden of diabetes [18,30,40].…”
Section: Memory Attention and Decision Processes (34 Studies)mentioning
confidence: 99%
“…Themes: Short-term effects of screening (11 studies) and concerns about the harmful effect of the screening procedure (four studies). Some people with diabetes reported that screening has negative short-term effects, for example, some dislike mydriatic eye drops (given to temporarily dilate the pupils) [32,55,59], which were often uncomfortable or, in some cases, painful [28,30,38]. In one case a woman had developed a phobia of these eye drops [25].…”
Section: Beliefs About Consequences (26 Studies)mentioning
confidence: 99%
“…Despite efforts to conceal the true nature of the study, asking about self-management behaviour from the outset may have elicited a social desirability bias, of which younger people are considered susceptible (26). Accuracy of self-report is also vulnerable to recall bias, particularly in the light of acknowledged confusion regarding the difference between screening for DR and a standard eye check (29). Future studies could overcome risk of bias by not only including definition of screening (as was done in the current study) but also corroboration of self-report with clinical record data (35).…”
Section: Summary Of Findingsmentioning
confidence: 99%